Түшээ гүн Чагдаржав ба Хятад, Opoc, Монгол гурван улсын 1915 оны Хиагтын гэрээ - О, Батсайхан (Journal of International Studies, 2001)
English title: Tushee graf Chagdarjav and agreement of three parties Russia, China and Mongolia in 1915